Analysis of microbial community biodiversity in activated sludge from a petrochemical plant - Antunes,Themis Collares (2021)
Abstract The active sludge process is one of the most-used techniques for the biodegradation of organic compounds present in effluents from an assortment of wastewaters. This study investigated the bacterial community structure of a petroleum industry’s activated sludge and its physical and chemical parameters using high-throughput sequencing. Samples were collected over one year: autumn 2015 (C1), winter 2015 (C2), spring 2015 (C3), and summer 2016 (C4). Total DNA was extracted, and the primers targeting the V4 region of the 16S rRNA gene were used for amplicon sequencing. The majority of the detected microorganisms were considered rare microbiota, presenting a relative abundance below 1% of the total sequences. All of the sequences were classified at the phylum level, and up to 55% of the ASVs (Amplicon Sequence Variants) were associated with known bacterial genera. Proteobacteria was the most abundant phylum in three seasons, while the phylum Armatimonadota dominated in one season. The genus Hyphomicrobium was the most abundant in autumn, winter and summer, and an ASV belonging to the family Fimbriimonadaceae was the most abundant in the spring. Canonical Correspondence Analysis showed that physicochemical parameters of SS, SD and TSS are correlated, as well as ammoniacal nitrogen. Sample C3 presented the highest values of COD, AN and solids (SS, SD and TSS). The highest COD, AN, and solids values are correlated to the high frequency of the phylum Armatimonadota in C3.